PA.33 How well are we debriefing patients after interventional deliveries? A patient safety improvement project. (9th June 2014) - Tan, M; Mustafa, H
Abstract : Background: To assess how well the obstetric team at the Simpsons Centre for Reproductive Health, Edinburgh, were at debriefing patients after interventional deliveries prior to discharge. Interventional deliveries (e.g. caesarean sections, forceps, kiwi) can be traumatic experiences leading to a negative birth experience. Debriefing patients postnatally where aspects of the event are discussed can help decrease the negative birth experience. Method: The clinical notes of 25 random patients who had interventional deliveries in a 4 week period in 2013 were examined to determine whether they had a documented debrief. A brief intervention whereby a reminder message was read out at the daily team "safety brief" was implemented for one week thereafter. The project was then repeated after the daily reminder with a further 25 patients. Results: Initially, 5 (20%) of patients were debriefed by a doctor prior to discharge, of which 4 (80%) were by the obstetrician who performed the procedure. After the reminder in the daily team "safety brief", 10 (40%) of patients were debriefed, of which 10 (100%) were by the obstetrician who performed the procedure. Conclusion: There was a 50% improvement in the compliance of debriefing patients by obstetric staff. However, there is still room for improvement as well as determining if this improvement is sustainable for the future.